Social Media and Radicalization: The Latest Threat to Religious Moderation - Gani, Abdul; Fattah, Abdul; Nasri, Ulyan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This research explores the impact of social media on radicalization and its implications for religious moderation. The research background reflects a shift in communication paradigms in the digital society, increasing vulnerability to radical ideologies. The research aims to analyze how social media serves as a primary channel for the dissemination of radical ideologies and identify moderation strategies that can be applied. The research methodology involves a critical analysis of scholarly literature discussing the role of social media in the radicalization process. Data collection techniques include searching and reviewing relevant articles, books, and scholarly papers. Data analysis is conducted through a thematic approach to identify patterns, trends, and conceptual relationships. The research findings highlight the complexity of radicalization challenges in the era of social media, emphasizing the importance of a profound understanding of online dynamics to design effective moderation responses. The research conclusion underscores the need for cross-sector collaboration and joint efforts to address this radicalization threat. The implications of this research include the necessity for proactive public policies to monitor and regulate online content and promote critical digital literacy. Overall, this research provides valuable insights for developing adaptive and responsive religious moderation strategies in the current dynamics of social media.